Respuesta :
QUESTION 1
We want to solve,
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-6x+8}[/tex]
We factor the denominator of the fraction on the right hand side to get,
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-4x - 2x+8}.[/tex]
This implies
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x(x-4) - 2(x - 4)}.[/tex]
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{(x-4)(x - 2)}[/tex]
We multiply through by LCM of
[tex](x-4)(x - 2)[/tex]
[tex](x - 2) + x(x-4) = 2[/tex]
We expand to get,
[tex]x - 2 + {x}^{2} - 4x= 2[/tex]
We group like terms and equate everything to zero,
[tex] {x}^{2} + x - 4x - 2 - 2 = 0[/tex]
We split the middle term,
[tex] {x}^{2} + - 3x - 4 = 0[/tex]
We factor to get,
[tex] {x}^{2} + x - 4x- 4 = 0[/tex]
[tex]x(x + 1) - 4(x + 1) = 0[/tex]
[tex](x + 1)(x - 4) = 0[/tex]
[tex]x + 1 = 0 \: or \: x - 4 = 0[/tex]
[tex]x = - 1 \: or \: x = 4[/tex]
But
[tex]x = 4[/tex]
is not in the domain of the given equation.
It is an extraneous solution.
[tex] \therefore \: x = - 1[/tex]
is the only solution.
QUESTION 2
[tex]\sqrt{x+11} -x=-1[/tex]
We add x to both sides,
[tex]\sqrt{x+11} =x-1[/tex]
We square both sides,
[tex]x + 11 = (x - 1)^{2} [/tex]
We expand to get,
[tex]x + 11 = {x}^{2} - 2x + 1[/tex]
This implies,
[tex] {x}^{2} - 3x - 10 = 0[/tex]
We solve this quadratic equation by factorization,
[tex] {x}^{2} - 5x + 2x - 10 = 0[/tex]
[tex]x(x - 5) + 2(x - 5) = 0[/tex]
[tex](x + 2)(x - 5) = 0[/tex]
[tex]x + 2 = 0 \: or \: x - 5 = 0[/tex]
[tex]x = - 2 \: or \: x = 5[/tex]
But
[tex]x = - 2[/tex]
is an extraneous solution
[tex] \therefore \: x = 5[/tex]
We want to solve,
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-6x+8}[/tex]
We factor the denominator of the fraction on the right hand side to get,
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x^{2}-4x - 2x+8}.[/tex]
This implies
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{x(x-4) - 2(x - 4)}.[/tex]
[tex]\frac{1}{(x-4)}+\frac{x}{(x-2)}=\frac{2}{(x-4)(x - 2)}[/tex]
We multiply through by LCM of
[tex](x-4)(x - 2)[/tex]
[tex](x - 2) + x(x-4) = 2[/tex]
We expand to get,
[tex]x - 2 + {x}^{2} - 4x= 2[/tex]
We group like terms and equate everything to zero,
[tex] {x}^{2} + x - 4x - 2 - 2 = 0[/tex]
We split the middle term,
[tex] {x}^{2} + - 3x - 4 = 0[/tex]
We factor to get,
[tex] {x}^{2} + x - 4x- 4 = 0[/tex]
[tex]x(x + 1) - 4(x + 1) = 0[/tex]
[tex](x + 1)(x - 4) = 0[/tex]
[tex]x + 1 = 0 \: or \: x - 4 = 0[/tex]
[tex]x = - 1 \: or \: x = 4[/tex]
But
[tex]x = 4[/tex]
is not in the domain of the given equation.
It is an extraneous solution.
[tex] \therefore \: x = - 1[/tex]
is the only solution.
QUESTION 2
[tex]\sqrt{x+11} -x=-1[/tex]
We add x to both sides,
[tex]\sqrt{x+11} =x-1[/tex]
We square both sides,
[tex]x + 11 = (x - 1)^{2} [/tex]
We expand to get,
[tex]x + 11 = {x}^{2} - 2x + 1[/tex]
This implies,
[tex] {x}^{2} - 3x - 10 = 0[/tex]
We solve this quadratic equation by factorization,
[tex] {x}^{2} - 5x + 2x - 10 = 0[/tex]
[tex]x(x - 5) + 2(x - 5) = 0[/tex]
[tex](x + 2)(x - 5) = 0[/tex]
[tex]x + 2 = 0 \: or \: x - 5 = 0[/tex]
[tex]x = - 2 \: or \: x = 5[/tex]
But
[tex]x = - 2[/tex]
is an extraneous solution
[tex] \therefore \: x = 5[/tex]